Metaphotonics with subwavelength dielectric resonators - Mikhail V. Rybin; Yuri Kivshar (npj Nanophotonics, 2024)
Abstract The recently emerged Mie resonant meta photonics (or Mietronics) provides novel opportunities for subwavelength optics. Mietronics employs resonances in isolated nanoparticles and structured surfaces. We present a brief summary of the key concepts underpinning this rapidly developing area of research, using isolated high-index dielectric subwavelength particles as examples. We also discuss recent advances and future trends in the designs of high-Q elements for efficient resonant spatial and temporal control of light.